Environmental Ethics in the Qur’an and Modern Mining Practices: A Case Study of PT Freeport Indonesia - Oktavia Nur Fadhilla; Dede Rodin; Muhammad Saifullah (Universitas Pakuan, 2026)
This article examines the concept of ecology in the Qur'an with an emphasis on the principles of khalifah, mīzān, amanah, and the prohibition of fasād as the basis for environmental management ethics. This study aims to assess the phenomenon of environmental damage occurring in the operational area of PT Freeport Indonesia through the perspective of Islamic ecology. The method used is qualitative research with a thematic interpretation approach, which integrates classical and contemporary interpretation studies as well as theoretical analysis of green economics and stewardship. The results show that the Qur'an not only provides normative guidelines but also an analytical framework for evaluating extractive industry practices. Various forms of environmental degradation, such as tailings management, landscape changes, and water quality deterioration, suggest a discrepancy between mining practices and the ecological ethical principles outlined in the Qur'an. These conditions reflect a disruption of the principle of balance (mīzān), the suboptimal implementation of the caliphate mandate, and the emergence of indications of structural fasād. This study affirms the relevance of thematic interpretation of the Qur'an as a critical approach in the study of Islamic ecology and sustainable natural resource management.